Coincident particle and optical observations of nightside subauroral proton precipitation. Issue 3 (19th March 2013) - Søraas, Finn; Laundal, Karl M.; Usanova, Maria
Abstract : [1] We report two instances of nightside subauroral proton precipitation observed during a geomagnetic storm: (1) An arc at 蝶 50° magnetic latitude (MLAT), which extended roughly from midnight to 6 magnetic local time (MLT), and (2) A corotating spot at 51.5° MLAT, postmidnight. The proton precipitation was observed by both the IMAGE SI‐12 proton aurora (Doppler‐shifted Lyman‐ α ) imager, and low‐altitude Polar‐orbiting Operational Environmental Satellites (POESs) that serendipitously traversed both the arc and the spot, providing in situ particle measurements. The Lyman‐alpha emission and the particle observations match closely. The particle measurements showed that the energies of the precipitating protons extended to several hundred keV, but no enhancements in the protons below 20 keV were observed. Cluster observations showed that the ring current contained protons with energies extending from tens of eV to several hundred keV; thus, the particles are scattered into the atmosphere from an existing reservoir. Outside the luminous regions, but at the same magnetic latitude, the POES satellites observed localized regions with enhanced proton fluxes outside, but close to, the loss cone. This shows that the protons along a large region in MLT are subjected to pitch angle scattering. Model calculations of the plasmasphere show that the arc and the proton precipitation are located just inside the plasmapause. The intensity and longitudinal extension of the arc are modulated by the dynamical pressure in the solar wind. In the dusk sector, ground stations recorded electromagnetic ion cyclotron waves associated with localized proton precipitation just inside the plasmapause. This suggests that the proton precipitation is caused by wave/particle interaction. Key points: Sub‐auroral proton aurora is reported, with coincident in‐situ measurements The pitch angle scattering extends beyond the luminous regions The location of the precipitation suggests a relation to EMIC waves